Galaxolide-contaminated soil and tolerance strategies in soybean plants using biofertilization and selenium nanoparticle supplementation - Halawani, Riyadh F.; Aloufi, Fahed A. (Frontiers in Plant Science, 2023)
The current study aimed to address the response of soybean (Glycine max) plants to biofertilization and selenium supplementation treatments under galaxolide contamination of soil. In this regard, a pot experiment was carried out where the soybean plants were treated with the plant growth-promoting Actinobacteria (Actinobacterium sp.) as a biofertilizer (PGPB treatment) and/or selenium nanoparticles (Se treatment; 25 mg L -1 ) under two non-polluted and galaxolide-polluted soils (250 mg galaxolide per kg of soil) to assess the modifications in some plant physiological and biochemical traits. Although higher accumulation of oxidative biomarkers, including hydrogen peroxide (+180%), malondialdehyde (+163%), and protein oxidation (+125%), indicating oxidative stress in galaxolidecontaminated plants, an apparent decline in their contents was observed in response to biofertilization/supplementation treatments in contaminated soil, especially. It was mainly related to the higher detoxification of ROS in PGPB-and Se-treated plants under galaxolide-induced oxidative stress, in which the direct ROS-scavenging enzymes (+44 -179%), enzymatic (+34 -293%) and nonenzymatic (+35 -98%) components of the ascorbate-glutathione pathway, and antioxidant molecules (+38 -370%) were more activated than in control plants. In addition, a higher accumulation of detoxification activity markers, including phytochelatins (+32%) and metallothioneins (+79%), were found in the combined treatments (PGPB+Se) under galaxolide contamination. Moreover, combined treatment with PGPB and Se ameliorated the levels of chlorophyll a content (+58%), stomatal conductance (+57%), the maximum efficiency of photosystem II (PSII) (+36%), and photorespiratory Field Code Changed metabolism (including +99% in glycolate oxidase and +54% in hydroxypyruvate reductase activity) in leaves under galaxolide contamination, which resulted in higher photosynthesis capacity (+36%) and biomass production (+74%) in galaxolide-stressed plants as compared to control group. In conclusion, the application of beneficial Actinobacteria and selenium nanoparticles as biofertilization/supplementation is expected to be useful for improving plant toleration and adaptation against galaxolide contamination.